Microbiota and gastric cancer: from molecular mechanisms to therapeutic strategies - Chen, Zhou; Jin, Dacheng; Hu, Jinjing; Guan, Defeng; Bai, Qizhou; Gou, Yunjiu (Frontiers in Cellular and Infection Microbiology, 2025)
Gastric cancer, a prevalent malignancy globally, is influenced by various factors. The imbalance in the gut microbiome and the existence of particular intratumoural microbiota could have a strong connection with the onset and progression of gastric cancer. High-throughput sequencing technology and bioinformatics analysis have revealed a close correlation between abnormal abundance of specific microbial communities and the risk of gastric cancer. These microbial communities contribute to gastric cancer progression through mechanisms including increasing cellular genomic damage, inhibiting DNA repair, activating abnormal signaling pathways, exacerbating tumor hypoxia, and shaping a tumor immune-suppressive microenvironment. This significantly impacts the efficacy of gastric cancer treatments, including chemotherapy and immunotherapy. Probiotic, prebiotic, antibiotic, carrier-based, dietary interventions, fecal microbiota transplantation, and traditional Chinese medicine show potential applications in gastric cancer treatment. However, the molecular mechanisms regarding dysbiosis of microbiota, including gut microbiota, and intra-tumoral microbiota during the progression of gastric cancer, as well as the therapeutic efficacy of microbiota-related applications, still require extensive exploration through experiments.